PLATELET HEMOSTASIS DYNAMICS IN SIMVASTATINTREATED PATIENTS WITH ARTERIAL HYPERTENSION AND DYSLIPIDEMIA - I. N. Medvedev; I. A. Skoryatina (Российский кардиологический журнал, 2010)
Aim: To assess simvastatin effectiveness in lipid profile and platelet activity correction among patients with arterial hypertension (AH) and dyslipidemia. Material and methods. In total, 34 patients received simvastatin for 4 months. The dynamics of lipid profile, lipid peroxidation in plasma and platelets, blood and platelet antioxidant protection, and platelet activity was assessed. The statistical methods included Student t-test and correlation analysis. Results. Simvastatin corrected dyslipidemia and lipid peroxidation, as well as optimised intra-platelet mechanisms of platelet function regulation, in AH patients with dyslipidemia. Simvastatin also inhibited increased platelet activation in vitro. Conclusion. Long-term simvastatin therapy resulted in stable positive effects among patients with AH and dyslipidemia.